Transparency of Papua's Special Autonomy Funds: Is It Possible? - Sarjito, Aris (Program Studi Ilmu Pemerintahan Universitas Islam Raden Rahmat Malang, 2025)
Abstract This qualitative research examines the current state of transparency in the management of Papua's special autonomy funds, aiming to unveil the challenges impeding transparency and propose strategies for enhancement. Utilizing secondary data analysis, the study investigates transparency practices, disclosure mechanisms, and the availability of relevant data. Findings reveal significant challenges, including bureaucratic hurdles, legal ambiguities, weak oversight mechanisms, and resistance to transparency initiatives, hindering transparency in fund management. Despite these challenges, the research identifies feasible strategies for enhancing transparency, such as establishing comprehensive disclosure mechanisms, strengthening oversight, engaging stakeholders, and implementing capacity-building initiatives. The study concludes that while achieving transparency in Papua's special autonomy funds poses challenges, it is indeed possible through concerted efforts and strategic interventions. Keywords: accountability, governance, Papua, special autonomy funds, transparency